Are cam morphology size and location associated with self‐reported burden in football players with FAI syndrome?. (24th January 2022) - Scholes, Mark J.; Kemp, Joanne L.; Mentiplay, Benjamin F.; Heerey, Joshua J.; Agricola, Rintje; King, Matthew G.; Semciw, Adam I.; Lawrenson, Peter R.; Crossley, Kay M.
Abstract: Cam morphology size and location might affect the severity of reported burden in people with femoroacetabular impingement (FAI) syndrome. We investigated the relationship between cam morphology size (i.e., alpha angle) and self‐reported hip/groin burden (i.e., scores for the International Hip Outcome Tool‐33 (iHOT‐33) and Copenhagen Hip and Groin Outcome Score (HAGOS)), examined separately for the anteroposterior pelvis (AP) and Dunn 45° radiographs in football players with FAI syndrome. In total, 118 (12 women) subelite football (soccer or Australian football) players with FAI syndrome with cam morphology (alpha angle ≥60°) participated. One blinded assessor quantified superior and anterosuperior cam morphology size by measuring alpha angles for the AP and Dunn 45° radiographs, respectively. Linear regression models investigated relationships between alpha angle (continuous independent variable, separately measured for the AP and Dunn 45° radiographs) and iHOT‐33 and HAGOS scores (dependent variables). Larger anterosuperior cam morphology (seen on the Dunn 45° radiograph) was associated with lower (i.e., worse) scores for the iHOT‐Total, iHOT‐Symptoms, iHOT‐Job, and iHOT‐Social subscales (unadjusted estimate range −0.553 to −0.319 [95% confidence interval −0.900 to −0.037], p  = 0.002 to 0.027), but not the iHOT‐Sport ( p  = 0.459) nor any HAGOS scores ( p  = 0.110 to 0.802). Superior cam morphology size (measured using the AP radiograph) was not associated with any iHOT‐33 or HAGOS scores ( p  = 0.085 to 0.975). Larger anterosuperior cam morphology may be more relevant to pain and symptoms in football players with FAI syndrome than superior cam morphology, warranting investigation of its effects on reported burden and hip disease over time.